PERANAN SISTEM PENGENDALIAN MANAJEMEN PADA PENGADAAN BARANG DAN JASA PEMERINTAH (STUDI KASUS PADA DINAS KESEHATAN KABUPATEN JENEPONTO) - Hesty Juniar Rukmin; Ansyarif Khalid; Samsul Rizal (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the Role of Management Control Systems in Procurement of Government Goods and Services in the Dinas Kesehatan Kabupaten Jeneponto. The type of data used in this study is qualitative data. Data collection techniques in this study are interviews, literature studies, and documentation. Data analysis method used in this research is Qualitative Descriptive. The results showed that the role of the management control system in the procurement of goods and services at the Dinas Kesehatan Kabupaten Jeneponto was good because the control system had the role of forming committees, implementing, monitoring and supervising the procurement of goods and services at the Dinas Kesehatan Kabupaten Jeneponto.